Factors influencing the removal of immune complex deposits from the renal glomerulus - Furness, Peter Norman (1988)
This thesis describes a study of the mechanisms involved in the elimination of established, morphologically identifiable electron dense deposits from the glomeruli of rats with chronic serum sickness. The initial experiments established the experimental model and evaluated the effects of variations in the method of administration, the antigen dose and charge, and the route of administration. The model was further characterized in terms of the progression of the morphological, functional and biochemical abnormalities induced.